Viscoelastic particle focusing based imaging flow cytometry: An application to yeast cells - Hong, Sun Ok; Choi, Bo Hyun; Lee, Pyung Cheon; Lee, Sung Sik; Kim, Ju Min (23rd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2019, 2019)
Flow cytometry is a tool to characterize individual cells continuously in flow. It is important to make a single stream of cells focused in the device to detect the signal from the cells efficiently. Here, we utilize the fluid viscoelasticity for 3D particle focused flow of cells. Since the fluid speed for focusing is relevantly slow, we could acquire image of moving cells in real time and could also obtain various information of the cells continuously. The viscoelastic particle focusing could be achieved in a simple geometry: straight rectangular channel, we expect that this approach can be applied to various microfluidic systems containing multiple functions under flow condition.
Keywords: Flow condition; Focused-flow; Individual cells; Micro fluidic system; Multiple function; Particle focusing; Rectangular channel; Simple geometries; Imaging flow cytometry; Microfluidics; Viscoelastic particle focusing